Kajian Aspek Populasi Menggunakan Model Pertumbuhan Allometri Spesies Kerang Kapah di Pantai Binalatung Kota Tarakan - Firman Firman; Gazali Salim (Journal Omni-Akuatika, 2016)
The research goal was to compare the shells types of Kapah (Meretrix meretrix; M. lyrata; Geloniacoaxans) that found in the Coast Binalatung area, Tarakan and to assess the growth of shellfishallometri. Sampling is done by making a transect along the coast Binalatung as much as 12 transects.Each transect arranged lengthwise along the beach with 25 meters of each transect. Sampling wascarried out in the absence of repetition with an area of 25 x 25 meters transect. Sampling was done byusing tools such as Kapah’ rakes. The result showed the M. meretrix constistes of 63 % of Kapah’spopulation while M. lyrata and G. coaxans represent 27 % and 10 % respectively. Growth comparisonbetween shell length and weight was considered as positive allometri while comparison between thickshells and weight of shellfish Kapah was allometri negative.Keywords: shellfish kapah, allometri growth, Binalatung, Tarakan